A Cost-Utility Analysis of Robotic Arm-Assisted Total Hip Arthroplasty: Using Robotic Data from the Private Sector and Manual Data from the National Health Service. (27th February 2022) - Clement, N. D.; Gaston, P.; Hamilton, D. F.; Bell, A.; Simpson, P.; Macpherson, G. J.; Patton, J. T.
Abstract : Purpose . The aim was to assess the cost-effectiveness of robotic arm-assisted total hip arthroplasty (rTHA) compared with manual total hip arthroplasty (mTHA) and to assess the influence of annual volume on the relative cost-effectiveness of rTHA. Methods . A database of both rTHA ( n  = 48 performed in a private centre) and mTHA ( n  = 512 performed in the National Health Service) was used. Patient demographics, preoperative Oxford hip score, forgotten joint score, EuroQol 5-dimensional 3-level (EQ-5D), and postoperative EQ-5D were recorded. Two models for incremental cost-effectiveness ratios using cost per quality-adjusted life year (QALY) for rTHA were calculated based on a unit performing 100 rTHAs per year: 10-year follow-up and a lifetime time horizon (remaining life expectancy of a 69-year-old patient). Results . When adjusting for confounding factors, rTHA was independently associated with a 0.091 (p = 0.029 ) greater improvement in the EQ-5D compared to mTHA. This resulted in a 10-year time horizon cost per QALY for rTHA of £1, 910 relative to mTHA, which increased to £2, 349 per QALY when discounted (5%/year). When using the 10-year time horizon cost per QALY was approximately £3, 000 for a centre undertaking 50 rTHAs per year and decreased to £1, 000 for centre undertaking 200 rTHAs per year. Using a lifetime horizon, the incremental unadjusted cost per QALY gained was £980 and £1432 when discounted (5%/year) for rTHA compared with mTHA. Conclusions . Despite the increased cost associated with rTHA, it was a cost-effective intervention relative to mTHA due to the associated greater health-related quality of health gain, according to the EQ-5D outcome measure.